Alisher Navoi's Analysis of Humorous Verses in "Khazayin Ulmaoni" - Lukmonovna , Jumayeva Shahlo (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
In this article, an attempt is made to analyze in detail the humorous verses in Alisher Navoi's collection "Khazayin ul Maoniy".